The mafic-ultramafic dykes in the Yanbian Terrane (Sichuan Province, SW China): Record of magma differentiation and emplacement in the Emeishan large igneous province - Munteanu, M.; Wilson, A.; Costin, G.; Yao, Y.; Lum, J.; Jiang, S.; Jourdan, Fred; Chunnett, G.; Cioaca, M. (Oxford University Press, 2017)
© The Author 2017. Published by Oxford University Press. All rights reserved. Numerous olivine-rich dykes intruded the late Proterozoic Yanbian terrane, Sichuan, SW China. The dykes are less than 10m thick and show thin aphanitic chilled margins (c. 10-20 cm wide), whereas most of the dyke volume comprises coarse porphyric rocks made up of olivine grains up to 2cm in size set in a groundmass consisting of clinopyroxene, plagioclase, Fe-Ti oxides, a second generation of olivine, hornblende and biotite. Chrome-spinel occurs mostly as inclusions in the olivine phenocrysts, but also in the groundmass. The geochemical investigation of 25 dykes suggested a meimechite-type composition of the coarse-grained rocks and a basaltic composition of the chill margins. The sum of REE contents is 46-67ppm in the coarse rock and 104-137 ppm in the chill margins. Chondrite-normalized REE and primitive mantle-normalized values show identical trends in all dykes, suggesting that they are comagmatic. The initial 87 Sr/ 86 Sr and eNd(t) (t=260Ma) of the dykes display values in the ranges 0.7041-0.7060 and 0.66-5.25, respectively. Olivine composition varies greatly, with Mg# values of 72.0-93.9. The Cr number of the spinel is 0.62-0.76. Clinopyroxene is Carich (0.76-0.89 Ca atoms per formula unit). Although 40 Ar/ 39 Ar investigations did not yield definitive results, the mineralogical and geochemical similarities between the studied dykes and the ultramafic lavas in the Emeishan large igneous province support their emplacement during Emeishan magmatism. Almost all elements unrelated to olivine (Ti, Al, Ca, P, Cu, Zr, Sr, Ba, Y, REE, U, Th, etc.) show strong positive inter-element correlation both in the chill margins and in the coarse-grained rocks, suggesting their concentration in the melt. The chilled margins (Mg#=55-63) would have been in equilibrium with moderately Mg-rich olivine (Mg# up to 84). Therefore, the Mg-rich olivine crystallized from a more primitive magma and was transported in the dykes by a more evolved melt with a composition similar to that of the chill margins. Flow differentiation could explain the concentration of the olivine phenocrysts in the inner parts of the dykes while some melt was expelled towards the dyke walls. Based on the composition of the most Mg-rich olivine, the Mg# of the primary magma was estimated to be 82-84. A meimechite-like composition for the primary magma (MgO=27-28%, FeO=10-11%, TiO 2 > 1%) was calculated by adding olivine with progressively higher magnesium number to the composition of the chill margins. The constraints of the mineral assemblage and simulations by MELTS modelling suggest magma evolution by olivine + Cr-spinel fractionation at P5 kbar. Elemental and Sr-Nd isotopic ratios indicate negligible crustal contamination. It is inferred that the primary magma resulted from the melting of a small fraction of mantle plume material in conjunction withmelting of S-depleted subcontinental lithospheric mantle material.